The first dinosaur : how science solved the greatest mystery on earth - Lendler, Ian (Margaret K. McElderry Books, 2019)
Tracks the history of fossil discovery, detailing how people explained the bones of dinosaurs, from claiming them to be giant humans or angels, to the scientific evolution that allowed scientists to make more accurate claims about the origins and nature of the discoveries. Pairs this evolution with commentary on the scientific process and the class, religious, and gender barriers that influenced discovery.